If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6x+16=8x+30
We move all terms to the left:
6x+16-(8x+30)=0
We get rid of parentheses
6x-8x-30+16=0
We add all the numbers together, and all the variables
-2x-14=0
We move all terms containing x to the left, all other terms to the right
-2x=14
x=14/-2
x=-7
| 6y=12B | | |5x-4|=|-2x-1| | | 9(x-5)=-15x+3 | | |-5x-4|=|-2x-1| | | 13x+6=-1x-8 | | t/2+15=18 | | x-100=6x+20 | | -3=d/4+-7 | | 6x^2+4x=10-7x | | n/4+5.6=3.85 | | 104=4-4(-1+3x) | | 155=5x+4(4x+2) | | 25-4x=-(x-26) | | 5=z/3+3 | | 1/3(6x+9)=5(2x-3) | | 5x+14=12+8x+2 | | -19c+20=-20c | | 39.16+0.50x=120 | | 67-u=212 | | 2x-100=6x+20 | | 10(-n)-1=29 | | -15-13s+1=18-11s | | 6n+4n-9n+5n=18 | | 10-x=1/3(3x-6) | | 120=39.16+0.50x | | 8d=4d+12 | | 6-18z=-5-19z | | 64=y/8 | | 9p-36=3p | | 15x-14+3x=10(x-1) | | 2h-12=-2h+4 | | u/3-3=5 |